IoT- New Perspectives and its Security - Raj, P. Herbert; Charles, P. Joseph; Mary, M. Merla Agnes (International Journal of Computer Sciences and Engineering, 2025)
After Cloud Computing a new development of technology is Internet of Things (IOT). The term IOT was coined by Kevin Ashton of Procter & Gamble in 1999.At that point, he viewed Radio-frequency identification (RFID) as essential to the Internet of things at that point which would allow computers to manage all individual things. IOT is a sort of “universal global neural network” in the cloud which connects various things. Other than the communication devices all the physical devices are all going to be connected to the Internet, and should be controlled by the wireless networks. Smart Things is another example in IT world. The Iot concept can be associated with Body Area Networks(BAN), Unmanned Aerial Vehicle networks and Satellite networks. The IoT creates and intellectual invisible network that can be controlled and detected. Future of Internet of Thingswill betransforming the real world objects into intelligent practical objects